BASIC CONCEPTS OF READING LITERACY AND ITS ROLE IN CHILD DEVELOPMENT FOR ELEMENTARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2024)
This article examines the importance of reading literacy for elementary school students and its impact on various aspects of child development — cognitive, social, and emotional. During the reading process, children are introduced to new words and concepts, which broadens their thinking horizon. Furthermore, learning about different cultures and lifestyles enriches their social understanding and enhances their ability to empathize.